Education Forums: resistance, limits and possibilities of action in the context of the COVID-19 Pandemic - Cleivane Reis; Cleidiana Parente (Universidade Federal do Norte do Tocantins, 2021)
The article seeks to reflect on the Education Forum institution, its competences, limits and possibilities in the context of the class struggle that is established in the field of educational policies. Taking dialectical historical materialism as a reference, a recent process of disputes around the national education policy is contextualized, in which the National Education Plan, the National Education Forum and the Education Conferences gain centrality, as instances where the struggle takes place of class by different projects of education and society. In the analysis, the Municipal Education Forums of Tocantins are taken as concrete references, as elements of the centralization-decentralization process of educational public policies at the national, state and municipal levels. The final considerations point out that in the context of the COVID-19 Pandemic, the conservative and neoliberal agenda emerges with more force, revealing the interests of the economic power of financial institutions, allying the media with the market, imposing an ultra-conservative agenda and a political agenda in international plan, which represents new challenges for the progressive field, in the organization of a plan of struggles in defense of public education, which cannot dispense with effective social participation in shaping an agenda aimed at guaranteeing the right to education for all.